2022
DOI: 10.3389/fendo.2022.996716
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet accumulation in β cells in patients with type 2 diabetes is associated with insulin resistance, hyperglycemia and β cell dysfunction involving decreased insulin granules

Abstract: Background and objectivePancreatic fat is a form of ectopic fat. Lipid droplets (LDs) are also observed in β cells; however, the pathophysiological significance, especially for β cell function, has not been elucidated. Our aim was to assess LD accumulation in β cells in various stages of glucose intolerance and to clarify its relationship with clinical and histological parameters.MethodsWe examined 42 Japanese patients who underwent pancreatectomy. The BODIPY493/503-positive (BODIPY-positive) area in β cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…21 In most cases, excessive weight gain gradually leads to the storage of surplus adipose tissue in non-adipose organs, including the pancreas, where fat accumulates intracellularly in both acinar and pancreatic islet cells, causing dysfunction. 21 The fatty replacement phase is characterized by an accumulation of intralobular fat in the form of lipid droplets in both endocrine and acinar cells, 34,35 provoking acinar cell…”
Section: Pathogenesismentioning
confidence: 99%
“…21 In most cases, excessive weight gain gradually leads to the storage of surplus adipose tissue in non-adipose organs, including the pancreas, where fat accumulates intracellularly in both acinar and pancreatic islet cells, causing dysfunction. 21 The fatty replacement phase is characterized by an accumulation of intralobular fat in the form of lipid droplets in both endocrine and acinar cells, 34,35 provoking acinar cell…”
Section: Pathogenesismentioning
confidence: 99%
“…Some studies found that IPFD was signifcantly associated with insulin resistance and β-cell function [13][14][15]; however, others hold a negative view [6,[16][17][18]. A recent study demonstrated that lipid droplet accumulation in β cells was associated with insulin resistance in T2DM individuals [19]. Ectopic fat deposition, including hepatic and pancreatic fat, was actuated by adipocyte dysfunction and elevated free fatty acids (FFAs) which were derived from triglyceride degradation, all of which might be involved in the process of insulin resistance [20].…”
Section: Discussionmentioning
confidence: 99%
“…concluded that accumulation of lipid droplets in β-cells was associated with insulin resistance which can lead to high levels of free fatty acids (FFAs) derived from degradation of triglycerides, the accumulated FFAs can flow into β-cell. In patients with T2DM due to insulin resistance, hyperglycemia combined with excess FFAs are linked to accumulation of lipid droplets in β-cell ( 16 ). Additionally, a longitudinal study which lasted for 15 years found that patients with familial combined hyperlipidemia were at high risk to develop T2DM ( 17 ).…”
Section: Discussionmentioning
confidence: 99%